2023
DOI: 10.1128/mbio.00414-23
|View full text |Cite
|
Sign up to set email alerts
|

CryoEM analysis of the essential native UDP-glucose pyrophosphorylase from Aspergillus nidulans reveals key conformations for activity regulation and function

Abstract: Invasive aspergillosis is one of the most serious clinical invasive fungal infections, resulting in a high case fatality rate among immunocompromised patients. The disease is caused by saprophytic molds in the genus Aspergillus , including Aspergillus fumigatus , the most significant pathogenic species. The fungal cell wall, an essential structure mainly composed of glucan, chitin, galactomannan, and galactosaminogalactan, represents an important target for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…396 (ii) base-to-base dimerization allowing tetramerization as observed in the AGPase from E. coli, 188 (iii) side-by-side parallel trimerization as in the case of GlmU from E. coli, 298 and (iv) top-to-top dimerization allowing octamerization as in eukaryotic UGPases. 397,398 5.1.1.1. ADP-Glucose Pyrophosphorylase.…”
Section: The Rossmann Foldmentioning
confidence: 99%
See 3 more Smart Citations
“…396 (ii) base-to-base dimerization allowing tetramerization as observed in the AGPase from E. coli, 188 (iii) side-by-side parallel trimerization as in the case of GlmU from E. coli, 298 and (iv) top-to-top dimerization allowing octamerization as in eukaryotic UGPases. 397,398 5.1.1.1. ADP-Glucose Pyrophosphorylase.…”
Section: The Rossmann Foldmentioning
confidence: 99%
“…413,414 UGPases are present in all kingdoms of life. 389 UGPase protomers comprise a canonical NSPase domain, with or without a C-terminal LβH domain, showing diverse forms of oligomerization, from monomers 415,416 to octamers 398,417,418 (Figures 10 and 11).…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our work aims at identifying unique structural and/or functional features that can be exploited for selective inhibition of the bacterial enzyme. In this regard, mechanistic differences linked to the respective quaternary structure are of specific interest: fungal and animal UGPs form octamers ( 31 35 ), and we previously demonstrated that octamerization is required for HsUGP function ( 29 , 36 ). In contrast, plant UGPs are active monomers but appear to be regulated by oligomerization ( 37 40 ), whereas protozoan UGPs form exclusively active monomers ( 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%